2019
DOI: 10.1186/s13046-019-1254-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MYOSLID promotes invasion and metastasis by modulating the partial epithelial-mesenchymal transition program in head and neck squamous cell carcinoma

Abstract: Background Partial epithelial mesenchymal transition (p-EMT) was found to play a potential role in the initial stage of metastasis in human head and neck squamous cell carcinoma (HNSCC). Some long noncoding RNAs (lncRNAs) have been reported to function as promoters or inhibitors of cancer metastasis. This study aimed to identify p-EMT-related lncRNAs in HNSCC. Methods Differentially expressed lncRNAs (DE-lncRNAs) and mRNAs (DEGs) in HNSCC obtained from The Cancer Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 30 publications
0
68
0
Order By: Relevance
“…We examined the correlation between the expression levels of the 42 differentially expressed lncRNAs and each differentially expressed mRNA using two-sided Pearson correlation coefficients and the z-test. The mRNAs positively or negatively correlated with the 42 lncRNAs were considered to be lncRNA-related mRNAs (|Pearson correlation coefficient| > 0.4 [16][17][18][19][20] and P-value <0.05). The lncRNA-mRNA co-expression network was then constructed using Cytoscape V.3.8.5 (https://cytoscape.org/).…”
Section: Construction Of Co-expression Networkmentioning
confidence: 99%
“…We examined the correlation between the expression levels of the 42 differentially expressed lncRNAs and each differentially expressed mRNA using two-sided Pearson correlation coefficients and the z-test. The mRNAs positively or negatively correlated with the 42 lncRNAs were considered to be lncRNA-related mRNAs (|Pearson correlation coefficient| > 0.4 [16][17][18][19][20] and P-value <0.05). The lncRNA-mRNA co-expression network was then constructed using Cytoscape V.3.8.5 (https://cytoscape.org/).…”
Section: Construction Of Co-expression Networkmentioning
confidence: 99%
“…Increasing evidence has proved lncRNAs play a rather crucial role in pathophysiological process including tumorigenesis [6][7][8][9][10]. LncRNAs regulate biological behaviors including cell proliferation, cell apoptosis, cell metastasis etc., during tumorigenesis [11][12][13]. For instance, lncRNA NORAD promoted cell proliferation by competitively binding with miR-155-5p [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that lncRNAs can serve as potential biomarkers for the early diagnosis and prognosis of multiple cancers, including HNSCC (Guglas et al, 2017;Li et al, 2019a). Recent reports have indicated that lncRNAs have multiple biological functions in HNSCC, including signaling regulation, invasion, metastasis, and potential prognostic biomarkers (Xiong et al, 2019;Zhang et al, 2019b). Qiu et al (2019) found that knockdown of RHPN1-AS1 inhibited cell migration, invasion and proliferation of HNSCC, indicating that RHPN1-AS1, acting as an oncogene, may be a potential diagnostic and therapeutic target in HNSCC.…”
Section: Introductionmentioning
confidence: 99%